The Application of Rules of Origin in Granting Preferential Concessions and Protecting International Trade - Haifaa Mezher Falhi, (Journal of Legal Sciences, 2024)
Rules of origin are considered one of the main pillars of great importance in customs work and their importance increases with the increase in economic agreements concluded by the state with the rest of the countries or with customs unions. With a view to facilitating and simplifying customs procedures and achieving efficiency in trade at the international level, and with a view to reducing disputes arising in the context of trade between States due to the origin of goods, vigorous efforts are being made at the international level to establish trade rules and bases in accordance with certain agreed standards, with a view to increasing consistency and simplification in the field of trade procedures and the exchange of goods, creating appropriate and common standards and trying to determine the effects that the application of rules of origin could have on the volume of trade between States. Where the rules of origin applied vary according to the agreements concluded between countries, and this is a problem that cannot be ignored, as exporters must be aware of all these rules in order to benefit from preferential advantages within the framework of the agreements concluded for the purpose of achieving mutual benefits in a balanced and reasonable manner. The subject of rules of origin and its subordinate concepts is a priority at the level of international institutions, especially the World Trade Organization and the World Customs Organization, for the purpose of finding consensual ways for the rules related to determining the country of origin at the international level, harmonizing them and making them flexible, easy and comprehensive in their use. Their application should not create additional administrative restrictions on the contracting parties, which has made the rules of origin an inevitable part of the current international trading system due to their importance in formulating the trade policy of countries and their important place in framing international trade. In this context, the Greater Arab Free Trade Area was embodied as an Arab trade agreement to confront the developments and international competition imposed by the new world order and to preserve and promote Arab economic interests in order to suit the multilateral international trade economic system and to achieve regional economic integration requires the coordination of frameworks for preferential treatment among Arab countries and the reduction of disputes arising within the framework of intra-international trade due to the identity of the commodity and national origin.